Carmen [opéra comique in four acts] - Bizet, Georges 1838-1875 (Opus Arte, 2008)
The Spanish gypsy Carmen lives only for sensuality. Love drives her from man to man. She encompasses the sergeant Don José with her wiles, and leads him to mutiny and desertion. Finally nothing remains for him but to join a band of smugglers of which Carmen is a member. His fate is endurable as long as he keeps hold of the love of Carmen, but when she turns from him he is sunk into despair
Extra features: costume design; illustrated synopsis; Choreographing Carmen; How to fight on stage; The cast and their characters; The gardens of Glyndebourne; booklet with new short story by novelist Jeanette Winterson. - Franz. gesungen, Untertitel engl., franz., dt. span. - Text d. Beih. engl., franz., dt. - Interpr.: Hans Voschezang [Moralès]. Lisa Milne [Micaela]. Marcus Haddock [Don José]. Jonathan Best [Zuniga]. Anne Sofie von Otter [Carmen]. Mary Hegarty [Frasquita]. Christine Rice [Mercédès]. Anthony Wise [Lilas Pastia]. Laurent Naouri [Escamillo]. Quentin Hayes [Le Dancaire]. Colin Judson [Le Remendado]. Franck Lopez [Le Guide]. Glyndebourne Chorus. London Philharmonic Orchestra. Philippe Jordan, conductor. Andrew George, choreographer
Keywords: Operas; Óperas; Film; DVD-Video